Preparation method of high-flexibility polyester modified epoxy electrophoretic paint
Patent Information
- Application Number
- CN202610957150.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
部分采用超支化聚酯或特殊固化剂的技术虽然可以改善涂膜某些性能,但原料成本较高、反应活性难以控制,容易影响槽液适用期和工业化稳定生产
[0020]与现有技术相比,本发明首先通过端羧基线性饱和聚酯多元醇与环氧树脂中的环氧基发生开环酯化反应,使聚酯柔性链段以共价键形式嵌入环氧树脂主链,而非以简单物理共混方式分散于树脂体系中;同时进一步引入聚碳酸酯二醇进行二次扩链,构建环氧-聚酯-聚碳酸酯嵌段共聚结构。该结构能够提高柔性链段在环氧树脂基体中的分散均匀性,降低涂膜固化过程中的微相分离倾向,使涂膜具有更好的链段运动能力和形变追随能力,从而显著提升涂膜柔韧性、耐冲击性和杯突性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathodic electrophoretic coating technology, and more specifically, to a method for preparing a highly flexible polyester-modified epoxy electrophoretic coating. Background Technology
[0002] Cathodic electrophoretic coating is a type of water-based anti-corrosion coating that uses water as the main dispersion medium and employs an external electric field to directionally deposit charged resin and pigments onto the surface of a metal substrate. Due to its advantages such as high coating efficiency, good penetration, uniform film, strong edge and corner coverage, high raw material utilization, and suitability for automated continuous production, cathodic electrophoretic coating has been widely used in the primer anti-corrosion treatment of automobile bodies, automotive parts, home appliances, construction machinery, and other metal products.
[0003] Currently, most industrially mature cathodic electrophoretic coatings use bisphenol A (BPA) type epoxy resin as the main resin. BPA type epoxy resin molecules contain structural units such as benzene rings and hydroxyl groups, exhibiting good adhesion to metal substrates. After curing, the coating film has a high crosslinking density and good corrosion resistance, chemical resistance, and mechanical strength. Therefore, epoxy-based cathodic electrophoretic coatings have long been the mainstream technology in automotive primer systems.
[0004] However, traditional bisphenol A epoxy resin coatings generally suffer from high rigidity, high internal stress, insufficient flexibility, and limited impact resistance after curing. For automotive body stampings, complex-shaped parts, thin sheet metal, bent parts, and metal substrates that may deform during assembly or service, the coating needs to have good deformation following ability. If the coating lacks flexibility, microcracks, decreased adhesion, or even localized peeling can easily occur during substrate bending, impact, vibration, or thermal expansion and contraction, thereby weakening the long-term anti-corrosion effect of the coating.
[0005] To improve the flexibility of epoxy electrophoretic coatings, existing technologies typically employ the following methods: First, introducing flexible segments into the main or side chains of the epoxy resin, such as polyether polyols, polyester glycols, polyester polyols, carboxyl-terminated liquid rubbers, or polyamine chain extenders; second, adding plasticizers, high-boiling-point co-solvents, or flexible resins with low glass transition temperatures to the coating system to reduce film rigidity; third, using hyperbranched polyesters, polyether-modified resins, or polyester-polyether composite modification systems to adjust the resin molecular structure and internal stress of the coating; and fourth, improving the overall mechanical properties of the coating by adjusting the curing agent structure, crosslinking density, and emulsion particle size distribution.
[0006] While the aforementioned modification methods can improve coating flexibility to some extent, they still have significant drawbacks. First, when improving flexibility by physically adding plasticizers or high-boiling-point co-solvents, the flexible component relies primarily on physical mixing with the epoxy resin matrix. During long-term use, migration, volatilization, or precipitation can easily occur, resulting in insufficient flexibility retention and potentially affecting coating hardness, solvent resistance, and corrosion resistance. Second, when using ordinary polyether or polyester flexible segments for chain extension modification, insufficient compatibility between the flexible segments and the epoxy resin can easily lead to microphase separation during curing, causing fluctuations in coating performance, manifested as unstable flexibility improvement, decreased coating density, and reduced salt spray resistance. Third, excessive introduction of flexible segments often lowers the glass transition temperature and crosslinking density of the resin system, sacrificing hardness, chemical resistance, and corrosion resistance while improving flexibility.
[0007] Furthermore, cathodic electrophoretic coatings are typically used in a weakly acidic aqueous dispersion system for long-term recycling, making bath stability particularly important for industrial applications. Existing flexible modified epoxy emulsions, after introducing more polyester or polyether segments, often exhibit problems such as increased emulsion particle size, wider particle size distribution, sedimentation, flocculation, viscosity changes, and a narrowing of the electrophoretic process window during storage or recycling. While some technologies employing hyperbranched polyesters or special curing agents can improve certain coating properties, they suffer from higher raw material costs and difficulty in controlling reactivity, potentially affecting the bath's service life and stable industrial production.
[0008] Therefore, how to effectively improve the flexibility and deformation following ability of the coating film without significantly sacrificing the adhesion, hardness, anti-corrosion performance and bath stability of epoxy electrophoretic coatings remains a technical problem that urgently needs to be solved in the field of cathodic electrophoretic coatings.
[0009] Therefore, it is necessary to propose a method for preparing highly flexible polyester-modified epoxy electrophoretic coatings to solve the above problems. Summary of the Invention
[0010] The purpose of this invention is to solve the technical problems mentioned in the background section and to provide a method for preparing a highly flexible polyester-modified epoxy electrophoretic coating.
[0011] The above-mentioned objective of this invention is achieved as follows: a method for preparing a highly flexible polyester-modified epoxy electrophoretic coating, comprising the following steps: S1. Under the protection of an inert gas, a polyacid, a polyol and an esterification catalyst are subjected to an esterification polycondensation reaction to obtain a carboxyl-terminated linear saturated polyester polyol. S2. Low molecular weight bisphenol A type epoxy resin, bisphenol A, the carboxyl-terminated linear saturated polyester polyol, and a first part of alkaline catalyst are reacted to allow the carboxyl-terminated linear saturated polyester polyol to embed into the epoxy resin backbone through a ring-opening esterification reaction between carboxyl groups and epoxy groups; then polycarbonate diol and a second part of alkaline catalyst are added for a secondary chain extension reaction; then a fully closed isocyanate curing agent and organic amine compound are added for an amination reaction, followed by neutralization with an organic acid neutralizing agent and emulsification with water to obtain a polyester-modified epoxy resin emulsion; S3. Mix and grind amine-modified epoxy polishing resin, carbon black, kaolin, anti-rust pigment, co-solvent and deionized water to obtain color paste; S4. The polyester-modified epoxy resin emulsion, the color paste, and deionized water are mixed and matured to obtain a high-flexibility polyester-modified epoxy electrophoretic coating.
[0012] As a preferred technical solution of the present invention, in step S1, the polyacid includes adipic acid and isophthalic acid, and the polyol includes 1,6-hexanediol and neopentyl glycol; wherein the molar ratio of carboxyl group to hydroxyl group is 1:(1.0-1.4), the molar ratio of adipic acid to isophthalic acid is (2-3):1, the molar ratio of 1,6-hexanediol to neopentyl glycol is (1-1.5):1, and the esterification catalyst is tetrabutyl titanate, the amount of which is 0.05%-0.15% of the total mass of the reactants.
[0013] As a preferred technical solution of the present invention, step S1 specifically includes: heating the reaction system to 158-162℃ and holding it at that temperature for 0.8-1.2 hours, then heating it to 178-182℃ and holding it at that temperature for 1.5-2.5 hours, and continuing to heat it to 208-212℃ until the acid value drops to 45-60 mgKOH / g, then removing residual moisture and low molecular weight volatiles under reduced pressure, and discharging the material after cooling; the number average molecular weight of the obtained carboxyl-terminated linear saturated polyester polyol is 1800-2800 g / mol, and the glass transition temperature is -25℃ to -15℃.
[0014] As a preferred technical solution of the present invention, in step S2, the raw materials for preparing the polyester modified epoxy resin emulsion, by weight, include: 65-75 parts of low molecular weight bisphenol A type epoxy resin, 12-20 parts of carboxyl-terminated linear saturated polyester polyol, 4-8 parts of polycarbonate diol, 10-15 parts of bisphenol A, 5-8 parts of xylene formaldehyde resin, 0.3-0.8 parts of alkaline catalyst, 18-25 parts of fully enclosed isocyanate curing agent, 6-10 parts of organic amine compound, 2-4 parts of organic acid neutralizer, 8-12 parts of alcohol ether cosolvent, and 85-100 parts of deionized water.
[0015] As a preferred technical solution of the present invention, step S2 includes: S21. Under inert gas protection, heat low molecular weight bisphenol A type epoxy resin, bisphenol A, and carboxyl-terminated linear saturated polyester polyol to 140-150℃, add the first part of alkaline catalyst accounting for 60%-70% of the total alkaline catalyst, heat the system to 175-185℃ and keep it at that temperature for 1.5-2.5 hours, and react until the acid value drops to below 3mgKOH / g. S22. Cool the system obtained in step S21 to 120-130℃, add polycarbonate diol and the remaining second part of alkaline catalyst, heat to 155-165℃ and keep the temperature for 1-2 hours to control the epoxy value at 0.85-0.95 meq / g. S23. Cool the product obtained in step S22 to 130-135℃, add a fully enclosed isocyanate curing agent and an organic amine compound, mix, and then perform an amination reaction at 80-100℃ for 1.5-2.5 hours. S24. Cool the amination resin obtained in step S23 to 60-70℃, add an alcohol ether co-solvent for dilution, then add an organic acid neutralizer for neutralization for 15-30 minutes, and add deionized water under stirring at 800-1500 rpm for reverse emulsification to obtain a polyester modified epoxy resin emulsion.
[0016] As a preferred embodiment of the present invention, the low molecular weight bisphenol A type epoxy resin is a liquid epoxy resin with an epoxy equivalent of 180-190 g / eq; the polycarbonate diol has a number average molecular weight of 1000-2000 g / mol; the alkaline catalyst is selected from at least one of triphenylphosphine, triethylamine, and N,N-dimethylbenzylamine; the organic amine compound is selected from at least one of diethanolamine, N-methyldiethanolamine, and diethylamine; the organic acid neutralizing agent is selected from at least one of lactic acid, acetic acid, and formic acid; and the alcohol ether co-solvent is selected from at least one of ethylene glycol butyl ether, propylene glycol methyl ether, and propylene glycol butyl ether.
[0017] As a preferred technical solution of the present invention, the fully enclosed isocyanate curing agent is an isophorone diisocyanate trimer or hexamethylene diisocyanate trimer with methyl ethyl ketone oxime or caprolactam as the sealing agent, and the desealing temperature of the fully enclosed isocyanate curing agent is 130-160℃.
[0018] As a preferred technical solution of the present invention, in step S3, the raw materials for preparing the color paste by weight include: 8-12 parts of amine-modified epoxy polishing resin, 2-4 parts of carbon black, 5-8 parts of kaolin, 1-3 parts of anti-rust pigment, 3-5 parts of propylene glycol butyl ether and 35-50 parts of deionized water; the grinding is carried out by using a sand mill to grind to a fineness of ≤15μm.
[0019] As a preferred technical solution of the present invention, in step S4, the mass ratio of the polyester modified epoxy resin emulsion to the color paste is (3-5):1. After adding deionized water, it is diluted to a solid content of 15%-20%, stirred evenly, and matured for 12-24 hours to obtain a high-flexibility polyester modified epoxy electrophoretic coating bath solution; wherein, the solid content of the polyester modified epoxy resin emulsion is 32%-38%, the average particle size is 60-120nm, and the pH value is 5.0-6.5.
[0020] Compared with existing technologies, this invention first involves a ring-opening esterification reaction between a carboxyl-terminated linear saturated polyester polyol and the epoxy groups in the epoxy resin. This allows the flexible polyester segments to be covalently embedded in the epoxy resin backbone, rather than being dispersed in the resin system through simple physical blending. Simultaneously, polycarbonate diol is further introduced for secondary chain extension, constructing an epoxy-polyester-polycarbonate block copolymer structure. This structure improves the uniformity of dispersion of the flexible segments in the epoxy resin matrix, reduces the tendency for microphase separation during coating curing, and gives the coating better segment mobility and deformation following ability, thereby significantly improving the coating's flexibility, impact resistance, and cupping properties.
[0021] Secondly, this invention controls the acid value, number-average molecular weight, and glass transition temperature of the carboxyl-terminated linear saturated polyester polyol, and combines this with the control of the epoxy value after secondary chain extension of polycarbonate diol. This ensures that the resin molecular weight increase, cationization reaction, and emulsification process remain within suitable ranges, which is beneficial for forming an aqueous dispersion emulsion with smaller particle size and narrower distribution. The polycarbonate diol segments have good hydrolysis resistance and structural stability, which can improve the emulsion stability during long-term operation of weakly acidic electrophoretic bath solutions, reducing problems such as particle size increase, sedimentation, and flocculation, thereby improving the storage and application stability of electrophoretic coatings.
[0022] Furthermore, both the polyester and polycarbonate flexible segments described in this invention participate in the construction of the resin molecular structure and remain stably present in the crosslinking network after curing. This improves the flexibility of the coating film while maintaining good adhesion, pencil hardness, solvent resistance, and salt spray resistance, avoiding the problem of overall performance degradation caused by the migration and precipitation of traditional plasticizers or low-molecular-weight flexible components. In addition, the preparation process of this invention does not rely on tin-containing heavy metal catalysts or large amounts of highly volatile organic solvents. The process conditions are mild, and the raw materials used are readily available for industrial procurement, making it suitable for large-scale implementation on existing epoxy electrophoretic coating production equipment. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0024] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Equivalent substitutions or conventional adjustments made by those skilled in the art to the types of raw materials, feeding ratios, reaction temperatures, reaction times, and process parameters without departing from the concept of the present invention should all fall within the scope of protection of the present invention.
[0025] The preparation process of the high-flexibility polyester-modified epoxy electrophoretic coating of this invention mainly includes the preparation of carboxyl-terminated linear saturated polyester polyol, the preparation of polyester-modified epoxy resin emulsion, the preparation of color paste, and the formulation of electrophoretic coating bath. By first embedding the carboxyl-terminated linear saturated polyester polyol into the epoxy resin backbone in the form of chemical bonds, and then introducing polycarbonate diol for secondary chain extension, the resin system forms an epoxy-polyester-polycarbonate block structure, thereby improving the problems of traditional epoxy electrophoretic coatings being hard and brittle and lacking flexibility, while also taking into account anti-corrosion performance, adhesion, hardness, and bath stability.
[0026] In this invention, the low molecular weight bisphenol A type epoxy resin can be a liquid epoxy resin with an epoxy equivalent of 180-190 g / eq, such as E51 or E44 type epoxy resin. The carboxyl-terminated linear saturated polyester polyol is preferably prepared by esterification and polycondensation reaction of adipic acid, isophthalic acid, 1,6-hexanediol, and neopentyl glycol. The polycarbonate diol is preferably a polycarbonate diol with a number average molecular weight of 1000-2000 g / mol, more preferably a polycarbonate diol based on 1,6-hexanediol. The fully blocked isocyanate curing agent can be an isophorone diisocyanate trimer or hexamethylene diisocyanate trimer using methyl ethyl ketone oxime or caprolactam as blocking agents.
[0027] Example 1: (a) Preparation of carboxyl-terminated linear saturated polyester polyols; In a reactor equipped with a stirrer, thermometer, water separator, and nitrogen inlet and outlet, 292g of adipic acid, 166g of isophthalic acid, 189g of 1,6-hexanediol, and 146g of neopentyl glycol were added, along with 0.4g of tetrabutyl titanate as an esterification catalyst. Nitrogen gas was introduced to replace the air in the reactor, and the mixture was stirred and heated under nitrogen protection.
[0028] The system was heated to 160℃ and held for 1 hour; then heated to 180℃ and held for 2 hours; finally, the temperature was increased to 210℃ for esterification polycondensation. Water was continuously separated during the reaction, and samples were taken periodically to test the acid value. When the acid value dropped to approximately 50 mg KOH / g, heating was stopped, residual moisture and low-molecular-weight volatiles were removed from the system under reduced pressure, and the product was cooled and discharged to obtain a carboxyl-terminated linear saturated polyester polyol.
[0029] The obtained carboxyl-terminated linear saturated polyester polyol was found to have a number-average molecular weight (Mn) of 2300 g / mol, a glass transition temperature (Tg) of -20℃, and an acid value of 51 mg KOH / g. This polyester polyol simultaneously contains adipic acid flexible aliphatic segments, isophthalic acid aromatic rigid structures, 1,6-hexanediol hexamethylene segments, and neopentyl glycol side methyl structures, which can improve its compatibility with epoxy resin systems while ensuring segment flexibility.
[0030] (II) Preparation of polyester-modified epoxy resin emulsion; Step 1: Primary chain extension of polyester blocks. Add 700g of E51 epoxy resin, 120g of bisphenol A, and 160g of the aforementioned carboxyl-terminated linear saturated polyester polyol to the reactor. Stir and heat to 145°C under nitrogen protection, then add 3.5g of triphenylphosphine. After adding the catalyst, the system temperature naturally rises to approximately 180°C, and the reaction is maintained at this temperature for 2 hours. During the reaction, the carboxyl groups of the carboxyl-terminated linear saturated polyester polyol undergo ring-opening esterification with the epoxy groups in the epoxy resin, causing the polyester segments to covalently embed into the epoxy resin backbone through ester bonds. Samples are taken to test the acid value; the primary chain extension reaction is terminated when the acid value drops to 1.8 mg KOH / g.
[0031] Step 2: Secondary chain extension of polycarbonate diol. The reaction system obtained in Step 1 was cooled to 125°C, and 60g of polycarbonate diol PCDL-1000 and 1.5g of triphenylphosphine were added. The temperature was then raised to 160°C and maintained for 1.5 hours. During this process, the hydroxyl groups at both ends of the polycarbonate diol molecule underwent a ring-opening etherification reaction with the epoxy groups in the system, further introducing flexible polycarbonate blocks into the polyester-modified epoxy resin. After the reaction, a sample was taken to determine the epoxy value, which was found to be 0.90 meq / g.
[0032] Step 3: Introduction of curing agent and amination reaction. The product obtained in Step 2 is cooled to 130°C, and 220g of fully blocked isocyanate curing agent and 80g of diethanolamine are added. After stirring and mixing thoroughly, the system temperature is controlled at 90°C, and the amination ring-opening reaction is carried out for 2 hours. This step is used to introduce the amine structure required for cationization into the resin molecular chain and to ensure that the blocked isocyanate curing agent is uniformly dispersed in the resin system.
[0033] Step 4: Neutralization and Emulsification. The amination resin obtained in Step 3 was cooled to 65°C, diluted with 100g of ethylene glycol butyl ether, followed by 25g of lactic acid, and stirred for neutralization for 20 minutes. Under high-speed stirring at 1200rpm, 950g of deionized water was slowly added to induce reverse emulsification, yielding a polyester-modified epoxy resin emulsion. The emulsion was found to have a solids content of 35.2%, an average particle size of 85nm, and a particle size distribution index (PDI) of 0.12.
[0034] (III) Preparation of color paste; 100g of amine-modified epoxy polishing resin, 30g of carbon black, 65g of kaolin, 20g of rust-preventive pigment, 40g of propylene glycol butyl ether, and 420g of deionized water were added to a dispersion container and pre-dispersed evenly. The mixture was then ground using a sand mill until the fineness was ≤15μm to obtain a color paste for electrophoretic coating. The rust-preventive pigment can be zinc phosphate, aluminum tripolyphosphate, or a combination thereof; zinc phosphate was used in this embodiment.
[0035] (iv) Preparation of electrophoretic coating solution; The above-mentioned polyester-modified epoxy resin emulsion and color paste were mixed at a mass ratio of 4:1, and deionized water was added to dilute it to a solid content of 18%. After stirring evenly, it was matured for 18 hours to obtain a high-flexibility polyester-modified epoxy electrophoretic coating bath.
[0036] Electrophoretic coating tests were conducted using the above-mentioned bath solution. A phosphated cold-rolled steel sheet was used as the cathode. Electrophoretic deposition was performed for 2.5 minutes at a bath temperature of 28°C and an electrophoretic voltage of 150V. After rinsing with water, the coating was baked and cured at 170°C for 25 minutes to obtain a coating with a thickness of 20±2μm.
[0037] Example 2: This example is basically the same as Example 1, except that the formulation of the carboxyl-terminated linear saturated polyester polyol is different. Specifically, 365g of adipic acid, 83g of isophthalic acid, 153g of 1,6-hexanediol and 166g of neopentyl glycol are added, and esterification polycondensation reaction is carried out according to the method described in Example 1 to obtain the carboxyl-terminated linear saturated polyester polyol.
[0038] Testing revealed that the number-average molecular weight (Mn) of the carboxyl-terminated linear saturated polyester polyol obtained in this embodiment was 2100 g / mol, the glass transition temperature (Tg) was -23°C, and the acid value was 55 mg KOH / g. The remaining steps for preparing the polyester-modified epoxy resin emulsion, the color paste, the electrophoretic coating bath, and the coating film preparation conditions were the same as in Example 1.
[0039] Example 3: This example is basically the same as Example 1, except for the type and amount of polycarbonate diol. In this example, PCDL-2000 with a number-average molecular weight Mn of 2000 g / mol is used, and the amount is 45 g. The remaining raw materials, preparation steps, reaction conditions, preparation method of electrophoretic coating bath, and coating film preparation conditions are the same as in Example 1.
[0040] Example 4: This example provides another method for preparing a highly flexible polyester-modified epoxy electrophoretic coating. The basic process is the same as that in Example 1, except that the formulations and process parameters of the carboxyl-terminated linear saturated polyester polyol, the polyester-modified epoxy resin emulsion, and the electrophoretic coating bath are different.
[0041] (a) Preparation of carboxyl-terminated linear saturated polyester polyols; In a reactor equipped with a stirrer, thermometer, water separator, and nitrogen inlet and outlet, 338g of adipic acid, 166g of isophthalic acid, 236g of 1,6-hexanediol, and 156g of neopentyl glycol were added, along with 1.2g of tetrabutyl titanate as an esterification catalyst. After purging the reactor with nitrogen to replace the air, the mixture was stirred and heated to 162°C under nitrogen protection, and the reaction was maintained at this temperature for 1 hour. The temperature was then increased to 182°C and maintained for 2 hours. Finally, the temperature was increased to 212°C for esterification polycondensation. Water was continuously separated during the reaction, and samples were taken periodically to test the acid value. When the acid value dropped to approximately 48mgKOH / g, residual water and low-molecular-weight volatiles were removed from the system under reduced pressure, and the mixture was cooled and discharged to obtain a carboxyl-terminated linear saturated polyester polyol.
[0042] According to the test results, the number-average molecular weight Mn of the carboxyl-terminated linear saturated polyester polyol obtained in this embodiment is 2500 g / mol, the glass transition temperature Tg is -18℃, and the acid value is 49 mg KOH / g.
[0043] (II) Preparation of polyester-modified epoxy resin emulsion; Step 1: Add 750g of E51 epoxy resin, 150g of bisphenol A, 200g of the above-mentioned carboxyl-terminated linear saturated polyester polyol, and 70g of xylene formaldehyde resin to the reactor. Stir and heat to 150℃ under nitrogen protection, add 4.0g of triphenylphosphine, and allow the system to heat naturally to 185℃. Maintain the temperature for 2 hours. Take a sample and test the acid value until it drops to 2.0mgKOH / g, thus ending one chain extension reaction.
[0044] Step 2: Cool the system to 130℃, add 80g of polycarbonate diol PCDL-1000 and 2.0g of triphenylphosphine, then heat to 165℃ and keep the temperature for 1 hour. Take a sample and measure the epoxy value to be 0.88 meq / g.
[0045] Step 3: Cool the product obtained in Step 2 to 135°C, add 250g of isophorone diisocyanate trimer curing agent blocked with methyl ethyl ketone oxime and 100g of diethanolamine, stir and mix evenly, then control the system temperature at 95°C and carry out the amination reaction for 2 hours.
[0046] Step 4: Cool the amination resin obtained in Step 3 to 70℃, add 120g of ethylene glycol butyl ether for dilution, then add 40g of lactic acid and stir to neutralize for 25 minutes. Under high-speed stirring at 1500rpm, slowly add 1000g of deionized water to perform reverse emulsification, obtaining a polyester-modified epoxy resin emulsion. The emulsion was found to have a solids content of 36.5%, an average particle size of 90nm, a particle size distribution index (PDI) of 0.13, and a pH of 5.8.
[0047] (III) Preparation of color paste; 120g of amine-modified epoxy grinding resin, 40g of carbon black, 80g of kaolin, 30g of zinc phosphate, 50g of propylene glycol butyl ether, and 500g of deionized water were added to a dispersion container and pre-dispersed evenly. The mixture was then ground in a sand mill until the fineness was ≤15μm to obtain a color paste.
[0048] (iv) Preparation of electrophoretic coating bath solution and preparation of coating film; The above-mentioned polyester-modified epoxy resin emulsion and color paste were mixed at a mass ratio of 5:1, and deionized water was added to dilute it to a solid content of 20%. After stirring evenly, it was matured for 24 hours to obtain a high-flexibility polyester-modified epoxy electrophoretic coating bath.
[0049] Using the above-mentioned bath solution, with a phosphated cold-rolled steel sheet as the cathode, electrophoretic deposition was carried out for 2.5 minutes at a bath temperature of 28°C and an electrophoretic voltage of 150V. After washing with water, the coating was baked and cured at 170°C for 25 minutes to obtain a coating with a thickness of 20±2μm.
[0050] Tests showed that the coating obtained in this embodiment had a flexibility of 1 mm, an impact resistance of 50 cm, a cupping value of 8.9 mm, an adhesion grade of 0, a pencil hardness of 2H, a MEK wiping resistance of >50 times, and a neutral salt spray resistance of 1030 hours. The bath solution showed no sedimentation, stratification, or gelation after being left at room temperature for 30 days.
[0051] Comparative Example 1: This comparative example is basically the same as Example 1, except that polycarbonate diol is not added, and the secondary chain extension step of polycarbonate diol in Example 1 is omitted. That is, after the primary chain extension reaction between the carboxyl-terminated linear saturated polyester polyol and epoxy resin is completed, the curing agent introduction, amination, neutralization emulsification, and subsequent color paste mixing and electrophoretic coating steps are directly carried out. The remaining raw materials and process conditions are the same as in Example 1.
[0052] Performance Testing: The coatings and emulsions obtained in Examples 1-4 and Comparative Example 1 were subjected to performance tests. Film thickness was tested according to GB / T13452.2-2008; flexibility was tested according to GB / T1731-2020; impact resistance was tested according to GB / T1732-2020; cupping was tested according to GB / T9753-2007; adhesion was tested according to GB / T9286-2021; pencil hardness was tested according to GB / T6739-2022; MEK swipe resistance was tested according to GB / T23989-2009; neutral salt spray resistance was tested according to GB / T1771-2007; emulsion particle size was tested using the dynamic light scattering method; the 30-day stability of the bath solution was evaluated by observing the presence of sedimentation, stratification, gelation, and significant particle size increase after standing at room temperature.
[0053] The test results for each embodiment and comparative example are as follows: Table 1 Comparison of coating performance of each embodiment and comparative example:
[0054] The test results above show that the coatings obtained in Examples 1-4 all achieved a flexibility of 1 mm, a cupping value of no less than 8.5 mm, and a neutral salt spray resistance time of over 1000 hours. Simultaneously, the adhesion remained at grade 0 and the pencil hardness remained at 2H. This indicates that the present invention improves the flexibility and deformation following ability of the coating without significantly sacrificing the adhesion, hardness, and corrosion resistance. Compared with Comparative Example 1, which did not introduce the polycarbonate diol secondary chain extender structure, Examples 1-4 showed superior performance in terms of cupping value, emulsion particle size, particle size distribution index, and 30-day stability of the bath solution. This demonstrates that polycarbonate diol, as a second flexible block, can effectively improve the dispersion uniformity of the resin emulsion and the overall mechanical properties of the coating.
[0055] The above results further illustrate that this invention, through the ring-opening esterification reaction of carboxyl-terminated linear saturated polyester polyol with epoxy resin, covalently embeds flexible polyester segments into the epoxy resin backbone; and further, through secondary chain extension of polycarbonate diol, introduces a second flexible block, forming an epoxy-polyester-polycarbonate block copolymer structure. This structure can reduce the tendency of flexible segments to separate into microphases in the cured coating, improve the uniformity of resin emulsion particle size distribution and bath stability, enabling the coating to maintain good salt spray resistance, adhesion, and hardness while possessing high flexibility, impact resistance, and cupping properties, thereby achieving synergistic optimization of flexibility, corrosion resistance, and construction stability.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a highly flexible polyester-modified epoxy electrophoretic coating, characterized in that, Includes the following steps: S1. Under the protection of an inert gas, a polyacid, a polyol and an esterification catalyst are subjected to an esterification polycondensation reaction to obtain a carboxyl-terminated linear saturated polyester polyol. S2. Low molecular weight bisphenol A type epoxy resin, bisphenol A, the carboxyl-terminated linear saturated polyester polyol, and a first part of alkaline catalyst are reacted to allow the carboxyl-terminated linear saturated polyester polyol to embed into the epoxy resin backbone through a ring-opening esterification reaction between carboxyl groups and epoxy groups; then polycarbonate diol and a second part of alkaline catalyst are added for a secondary chain extension reaction; then a fully closed isocyanate curing agent and organic amine compound are added for an amination reaction, followed by neutralization with an organic acid neutralizing agent and emulsification with water to obtain a polyester-modified epoxy resin emulsion; S3. Mix and grind amine-modified epoxy polishing resin, carbon black, kaolin, anti-rust pigment, co-solvent and deionized water to obtain color paste; S4. The polyester-modified epoxy resin emulsion, the color paste, and deionized water are mixed and matured to obtain a high-flexibility polyester-modified epoxy electrophoretic coating.
2. The preparation method according to claim 1, characterized in that, In step S1, the polyacids include adipic acid and isophthalic acid, and the polyols include 1,6-hexanediol and neopentyl glycol; wherein the molar ratio of carboxyl groups to hydroxyl groups is 1:(1.0-1.4), the molar ratio of adipic acid to isophthalic acid is (2-3):1, the molar ratio of 1,6-hexanediol to neopentyl glycol is (1-1.5):1, and the esterification catalyst is tetrabutyl titanate, the amount of which is 0.05%-0.15% of the total mass of the reactants.
3. The preparation method according to claim 2, characterized in that, Step S1 specifically includes: heating the reaction system to 158-162℃ and holding it at that temperature for 0.8-1.2 hours, then heating it to 178-182℃ and holding it at that temperature for 1.5-2.5 hours, and continuing to heat it to 208-212℃ until the acid value drops to 45-60 mgKOH / g. Then, the residual moisture and low molecular weight volatiles are removed under reduced pressure, and the material is discharged after cooling. The number average molecular weight of the obtained carboxyl-terminated linear saturated polyester polyol is 1800-2800 g / mol, and the glass transition temperature is -25℃ to -15℃.
4. The preparation method according to claim 1, characterized in that, In step S2, the raw materials for preparing the polyester-modified epoxy resin emulsion, by weight, include: 65-75 parts of low molecular weight bisphenol A type epoxy resin, 12-20 parts of carboxyl-terminated linear saturated polyester polyol, 4-8 parts of polycarbonate diol, 10-15 parts of bisphenol A, 5-8 parts of xylene-formaldehyde resin, 0.3-0.8 parts of alkaline catalyst, 18-25 parts of fully enclosed isocyanate curing agent, 6-10 parts of organic amine compound, 2-4 parts of organic acid neutralizer, 8-12 parts of alcohol ether cosolvent, and 85-100 parts of deionized water.
5. The preparation method according to claim 2, characterized in that, Step S2 includes: S21. Under inert gas protection, heat low molecular weight bisphenol A type epoxy resin, bisphenol A, and carboxyl-terminated linear saturated polyester polyol to 140-150℃, add the first part of alkaline catalyst accounting for 60%-70% of the total alkaline catalyst, heat the system to 175-185℃ and keep it at that temperature for 1.5-2.5 hours, and react until the acid value drops to below 3mgKOH / g. S22. Cool the system obtained in step S21 to 120-130℃, add polycarbonate diol and the remaining second part of alkaline catalyst, heat to 155-165℃ and keep the temperature for 1-2 hours to control the epoxy value at 0.85-0.95 meq / g. S23. Cool the product obtained in step S22 to 130-135℃, add a fully enclosed isocyanate curing agent and an organic amine compound, mix, and then perform an amination reaction at 80-100℃ for 1.5-2.5 hours. S24. Cool the amination resin obtained in step S23 to 60-70℃, add an alcohol ether co-solvent for dilution, then add an organic acid neutralizer for neutralization for 15-30 minutes, and add deionized water under stirring at 800-1500 rpm for reverse emulsification to obtain a polyester modified epoxy resin emulsion.
6. The preparation method according to claim 5, characterized in that, The low molecular weight bisphenol A type epoxy resin is a liquid epoxy resin with an epoxy equivalent of 180-190 g / eq; the polycarbonate diol has a number average molecular weight of 1000-2000 g / mol; the alkaline catalyst is selected from at least one of triphenylphosphine, triethylamine, and N,N-dimethylbenzylamine; the organic amine compound is selected from at least one of diethanolamine, N-methyldiethanolamine, and diethylamine; the organic acid neutralizing agent is selected from at least one of lactic acid, acetic acid, and formic acid; and the alcohol ether co-solvent is selected from at least one of ethylene glycol butyl ether, propylene glycol methyl ether, and propylene glycol butyl ether.
7. The preparation method according to claim 5, characterized in that, The fully enclosed isocyanate curing agent is an isophorone diisocyanate trimer or hexamethylene diisocyanate trimer with methyl ethyl ketone oxime or caprolactam as the sealing agent, and the desealing temperature of the fully enclosed isocyanate curing agent is 130-160℃.
8. The preparation method according to claim 1, characterized in that, In step S3, the raw materials for preparing the color paste, by weight, include: 8-12 parts of amine-modified epoxy polishing resin, 2-4 parts of carbon black, 5-8 parts of kaolin, 1-3 parts of anti-rust pigment, 3-5 parts of propylene glycol butyl ether, and 35-50 parts of deionized water; the grinding is carried out using a sand mill until the fineness is ≤15μm.
9. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of the polyester-modified epoxy resin emulsion to the color paste is (3-5):
1. After adding deionized water, it is diluted to a solid content of 15%-20%, stirred evenly, and matured for 12-24 hours to obtain a high-flexibility polyester-modified epoxy electrophoretic coating bath. The solid content of the polyester-modified epoxy resin emulsion is 32%-38%, the average particle size is 60-120nm, and the pH value is 5.0-6.5.